Antecedents and Consequences of Work Stress Behavior - Universari, Nuria; Harsono, Mugi (Universitas Semarang, 2021)
The purpose of this paper is to obtain a work stress model from scientific literature published from 2017 to 2020, where in one of the years, 2020, there was a covid-19 pandemic which had an impact on work stress. This study uses a literature review on work stress including antecedents, consequences, work stress management and the type of work/profession studied in research on work stress from 2017 to 2020. Based on the results of literature studies, the antecedents that most often appear in research on work stress are role conflict, workload, and leadership, while the consequences that often arise are burnout, job satisfaction/dissatisfaction, and intentions turnover. Work stress management involves individual and organizational levels. While the profession that has been mostly researched on the topic of work stress are paramedics and employees of the banking industry.